Comparative Analysis of the Fracture Resistance of a Polymeric Material for 3D Printing and a Milled Polymethylmethacrylate Material as Interim Material for Fixed Partial Dentures: New Material Updated - Cristian Abad-Coronel; Johanna Córdova; Andrea Merchán; Jaime Larriva; Ariana Bravo; Bryam Bernal; Cesar A. Paltán; Jorge I. Fajardo (Designs, 2023)
The aim of this study was to evaluate and compare the fracture resistance of a temporary three-unit fixed dental prosthesis (FDP) made of a new polymeric material obtained by an additive technique (3DPP) using a computer-aided design and manufacturing (CAD/CAM) system, comparing the prosthesis to the respective outcomes of temporary polymethylmethacrylate (PMMA) FDPs obtained by a subtractive technique (milling). Methods: Three-unit FDPs were 3D printed using a polymeric material (n = 20) or milled using polymethylmethacrylate (n = 20). After thermocycling at 5000 cycles at extreme temperatures of 5 °C and 55 °C in distilled water, each specimen was subjected to a compression test on a universal testing machine at a rate of 0.5 mm/min until failure occurred, recording the value in newtons (N). Results: There were statistically significant differences (p-value < 0.005) between the PMMA material (2104.7 N; SD = 178.97 N) and 3DPP (1000.8 N; SD = 196.4 N). Conclusions: The fracture resistance of the PDFs manufactured from milled PMMA showed higher values for fracture resistance. However, the resistance of the 3DPP showed acceptable values under mechanical load; this notable advance in the resistance of printed materials consolidates them as an important alternative to use in interim indirect restorations.